Early Interview of Speech Delay with Phonics Method in Children with Speech Delay Age 3 Years at Graha Husada Hospital Gresik - Rachmatus Salsabilah; Prianggi Amelasasih (Universitas Muhammadiyah Gresik, 2023)
Language disorders are delays in the language sector experienced by a child. A child can be said to have a delay in speaking if the child's level of speech development is below the level of quality of normal child's speech development in general according to his age, this can be seen from the correct use of words. The subject in this study with the initials MDE is 3 years old, this patient underwent routine therapy as much as twice a week. According to therapists who treat MDE, MDE is a child who has speech delay. The following are the results of researchers' observations of MDE who have speech delay. In this research, the phonics method is used, where the phonics method is